Pemberdayaan Bakti Sosial sebagai Pendidikan Mental kepedulian Masyarakat Indonesia pasa masa Pandemi Covid-19 - Alfi Putri Pramitasari; Ziyanatur Roziqoh; Wancuk Oktyonok; Lailatul Mafruhah Mafruhah; Ananda Fatya Setianingrum (Universitas Negeri Manado, 2021)
The purpose of this study is to empower social service as a mental education for the care of the Indonesian people during the Covid-19 pandemic. With the existence of this research data it can be used as a community service program and also a benchmark for society, especially in Indonesia, the community can empower social service during the current Covid-19 Pandemic and also this outbreak provides lessons to all people, especially the Indonesian people to open a spirit of concern. in society in order to face this covid-19 pandemic. At this time social service is still very seriously implemented. Therefore, it can be seen that when this outbreak entered the country of Indonesia from 2020 until now, the implementation of social service is very rampant by the government, organizations, associations, and others. At the beginning of the Covid-19 pandemic, the religious organization of the Al-Ikhlas Deltasari Mosque helped people who are well off to practice some of their assets to local residents so that they do not become haram assets and can be useful for residents who are more in need. There are several dozens of basic food packages that have been collected and ready to be distributed to residents around the Al-Ikhlas Deltasari Indah Mosque. This activity is carried out regularly every week, especially on Friday. This social service is not only in the form of basic necessities but also in the form of packaged rice, money and so on. The results obtained from the above social service activities are to help welfare, strengthen relationship with the surrounding community, foster a caring attitude among others, foster social sensitivity and provide happiness which are very important to carry out charity and social service activities, especially for less fortunate citizens. It is hoped that other communities can be inspired and raise awareness by holding similar activities. The method used in this community service program is to distribute packaged rice.